Occupation and the risk of hearing impairment - results from the Nord-Trøndelag study on hearing loss - Bo Engdahl; Kristian Tambs (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVES: We studied the effect of occupation on hearing and if it remained after adjustment for noise exposure, education, income, and other risk factors. METHODS: Audiometry and a questionnaire concerning exposure was administered to a general adult population sample in Norway (N=49 948). Information on occupation, education, and income was obtained from population census registers. RESULTS: Occupation had marked effects on hearing loss. Occupation explained 2-3% of the variance in hearing loss among men <45 years in addition to the hearing loss due to age (10-19%). Occupation explained ≤1% of hearing loss among women of all ages and young men. Controlling for self-reported occupational noise exposure reduced the occupational effect by 20-40% in men ≥45 years. Controlling for leisure-time noise, ear infections, and head injuries did not change the effect of occupation, which was slightly reduced after controlling for education and income. The most elevated hearing thresholds in men were observed among: wood workers; miners; linemen and cable jointers; construction carpenters and workers; seamen; and workshop mechanics. CONCLUSIONS: There was a moderate association between occupation and hearing loss. Unbiased estimates of occupational hearing loss may help identify high-risk occupations, for which interventions are needed, and identify individuals with hearing loss.